Workshop Optimasi Peran AI untuk Penyusunan Modul Ajar Deep Learning Bagi Guru IPA SMP di Kabupaten Muaro Jambi: Pengabdian - Harlis; Dara Mutiara Aswan; Asni Johari; M. Naswir; Retni S. Budiarti; M. Erick Sanjaya; Evita Anggereini (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Good planning is needed to facilitate the implementation of Deep Learning, so that learning ran optimally and could achieve learning outcomes. The existence of technology such as Artificial Intelligence (AI) could simplify teachers' work and save time in developing Deep Learning lesson plans. This community service activity aims to provided information related to the Deep Learning approach, AI tools that can be used in compiling Deep Learning lesson plan, and provided skills to teachers in using AI. This service activity was carried out at MGMP IPA Gugus 1 Muaro Jambi Regency. The method of implementation of the service was through lectures/seminars and tutorials on compiling Deep Learning lesson plans using AI. Through this activity, teachers received information related to the Deep Learning approach and AI tools that can be used to develop teaching modules and practiced in utilizing AI to compile Deep Learning lesson plans. It was concluded that this community service activity can improve the ability of science teachers who are members of MGMP IPA Gugus 1 Muaro Jambi Regency in utilizing AI to develop Deep Learning tlesson plans. This activity is expected to inspire the use of AI technology to improve the quality of learning.